Entrepreneurial behaviour and socio economic analysis of mushroom growers in Karnataka - SHIRUR, MAHANTESH; S, SHIVALINGEGOWDA N; J, CHANDREGOWDA M; RANA, RAJESH K (The Indian Journal of Agricultural Sciences, 2017)
Mushroom demand is showing tremendous growth worldwide due to its nutritional and medicinal qualities.In spite of huge potential and need to meet protein demand of large vegetarian population, India’s progress in mushroom entrepreneurship is not that impressive. Entrepreneurial behaviour along with other personal and socio-psychological traits of entrepreneurs plays a prominent role in achieving success in any enterprise. In the present study conducted among the mushroom growing entrepreneurs across Karnataka State, an effort was made to understand influence of identified variables on farmers’ entrepreneurial behaviour. Five attributes of farmers and their units, six attributes of socio-psychological traits and four extension variables were studied for investigating their effect on entrepreneurial behaviour of the respondents. Regression analysis showed that, academic qualification, cosmopolitanism, self-reliance, mass media participation, extension participation and training were significantly contributing to the entrepreneurial behaviour of the respondents.